Lipoprotein Lipase and PPAR Alpha Gene Polymorphisms, Increased Very-Low-Density Lipoprotein Levels, and Decreased High-Density Lipoprotein Levels as Risk Markers for the Development of Visceral Leishmaniasis by Leishmania infantum - Márcia Dias Teixeira Carvalho; Diego Peres Alonso; Célia Maria Vieira Vendrame; Dorcas Lamounier Costa; Carlos Henrique Nery Costa; Guilherme Loureiro Werneck; Paulo Eduardo Martins Ribolla; Hiro Goto (Mediators of Inflammation)
In visceral leishmaniasis (VL) endemic areas, a minority of infected individuals progress to disease since most of them develop protective immunity. Therefore, we investigated the risk markers of VL within nonimmune sector. Analyzing infected symptomatic and, asymptomatic, and noninfected individuals, VL patients presented with reduced high-density lipoprotein cholesterol (HDL-C), elevated triacylglycerol (TAG), and elevated very-low-density lipoprotein cholesterol (VLDL-C) levels. A polymorphism analysis of the lipoprotein lipase (LPL) gene using HindIII restriction digestion (N = 156 samples) (H+ = the presence and H− = the absence of mutation) revealed an increased adjusted odds ratio (OR) of VL versus noninfected individuals when the H+/H+ was compared with the H−/H− genotype (OR = 21.3; 95% CI = 2.32–3335.3; P = 0.003). The H+/H+ genotype and the H+ allele were associated with elevated VLDL-C and TAG levels (P < 0.05) and reduced HDL-C levels (P < 0.05). An analysis of the L162V polymorphism in the peroxisome proliferator-activated receptor alpha (PPARα) gene (n = 248) revealed an increased adjusted OR when the Leu/Val was compared with the Leu/Leu genotype (OR = 8.77; 95% CI = 1.41–78.70; P = 0.014). High TAG (P = 0.021) and VLDL-C (P = 0.023) levels were associated with susceptibility to VL, whereas low HDL (P = 0.006) levels with resistance to infection. The mutated LPL and the PPARα Leu/Val genotypes may be considered risk markers for the development of VL.